2022
DOI: 10.1037/fam0000901
|View full text |Cite
|
Sign up to set email alerts
|

Examining gender effects in postdivorce adjustment trajectories over the first year after divorce in Denmark.

Abstract: Research into gender and postdivorce mental and physical health has been highly inconsistent. The Gender Similarities Hypothesis suggests there are more similarities than differences and the Divorce Stress Adjustment Perspective suggests that structural inequalities may contribute to adverse postdivorce outcomes. We conducted secondary analyses from an RCT study to investigate if there were gender-specific trajectories and whether gender was associated with outcomes (self-perceived stress, symptoms of anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For divorce, this contrasts with previous research suggesting that divorce has stronger impact on men’s short-term wellbeing and women’s long-term income level, compared to the other gender [ 29 ]. However, a recent Danish study [ 47 ] did not find any gender-related differences in post-divorce trajectories between men and women. The authors argued that such gender differences were less likely to appear in egalitarian societies, such as the Danish.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For divorce, this contrasts with previous research suggesting that divorce has stronger impact on men’s short-term wellbeing and women’s long-term income level, compared to the other gender [ 29 ]. However, a recent Danish study [ 47 ] did not find any gender-related differences in post-divorce trajectories between men and women. The authors argued that such gender differences were less likely to appear in egalitarian societies, such as the Danish.…”
Section: Discussionmentioning
confidence: 97%
“…Leopold [ 29 ] investigated gender differences in outcomes following divorce over a 32-year period and found that men reported reduced well-being short-term compared to women, while women experienced stronger reduction in income long-term compared to men. However, other studies have not found gender differences in post-divorce and post-marriage trajectories (e.g., [ 47 , 48 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results must be interpreted with caution since the contradictory pattern of findings regarding gender differences in post‐divorce life satisfaction (Gustavson et al, 2012; Lucas, 2005; Næss et al, 2015). Data from recent longitudinal research have suggested that examining the interaction effect of gender with other sociodemographic characteristics may shed light on these opposing findings regarding a potential gender effect on life satisfaction (Leopold, 2018; Strizzi et al, 2022). For example, Leopold (2018) found that women reported higher life satisfaction immediately after divorce, but adaptation to post‐divorce developmental tasks alleviated gender differences in life satisfaction over time, with no differences between women and men in medium and long‐term life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…These results must be interpreted with caution since the contradictory pattern of findings regarding gender differences in post-divorce life satisfaction (Gustavson et al, 2012;Lucas, 2005;Naess et al, 2015). Data from recent longitudinal research have suggested that examining the interaction effect of gender with other sociodemographic characteristics may shed light on these opposing findings regarding a potential gender effect on life satisfaction (Leopold, 2018;Strizzi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Loss challenges, relationship challenges, global challenges, challenges of illness, challenges of fi nancial well-being -these are what our respondents wrote about, and they are the foci of most research on family resilience (most oft en each challenge is considered separately). Th us, special characteristics of family resilience have been analyzed in relation to illness in the family (Saltzman, 2016); to loss (Barboza, 2021;Khatib, 2022); confl icts in the family and divorce (Mashego, 2014;Strizzi, 2022); financial diffi culties (Kholostova, 2018;Orthner, 2004;Raniga, 2016); to global challenges, including various problems, for example, military operations, natural disaster, migration (Denoy, 2019;Mawarpury, 2017); and low income, together with potentially fatal disease (Naidoo, 2022).…”
Section: Discussionmentioning
confidence: 99%